2007
DOI: 10.1002/acp.1420
|View full text |Cite
|
Sign up to set email alerts
|

Durable and generalized effects of spatial experience on mental rotation: gender differences in growth patterns

Abstract: This study addressed questions about improvement in mental rotation skills: (1) whether growth trajectories differ for men and women with higher or lower spatial experience, (2) whether videogame training has effects on performance and leads to transfer, (3) whether effects of repeated testing or training effects are durable and (4) whether transfer is durable. Undergraduates participated in repeated testing on the MRT or played the videogame Tetris. Analyses showed large improvements in mental rotation with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
211
2
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(236 citation statements)
references
References 33 publications
18
211
2
5
Order By: Relevance
“…However, fast visuomotor control is necessary and, after practice, a shift from controlled to automatic processing (Schneider & Chein, 2003) occurs, resulting in improved play. Proficiency in Tetris does transfer to similar tasks such as mental rotation (De Lisi & Wolford, 2002;Sims & Mayer, 2002;Terlecki Newcombe, & Little, 2008), but playing Tetris does not develop basic skills like spatial selective attention (Green & Bavelier, 2003) or dissimilar skills like multiple-object tracking (Green & Bavelier, 2006). Indeed, Sims and Mayer (2002) concluded that "Tetris is a game whose component skills are somewhat separate from other kinds of spatial skills."…”
Section: Video Games As Training Toolsmentioning
confidence: 99%
“…However, fast visuomotor control is necessary and, after practice, a shift from controlled to automatic processing (Schneider & Chein, 2003) occurs, resulting in improved play. Proficiency in Tetris does transfer to similar tasks such as mental rotation (De Lisi & Wolford, 2002;Sims & Mayer, 2002;Terlecki Newcombe, & Little, 2008), but playing Tetris does not develop basic skills like spatial selective attention (Green & Bavelier, 2003) or dissimilar skills like multiple-object tracking (Green & Bavelier, 2006). Indeed, Sims and Mayer (2002) concluded that "Tetris is a game whose component skills are somewhat separate from other kinds of spatial skills."…”
Section: Video Games As Training Toolsmentioning
confidence: 99%
“…One such factor may lie in males experiencing more activities that involve spatial thinking compared to females (such as playing video games [79][80][81]). Another factor is suggested by studies [82,83], showing that instruction-induced expectations Running head: DEVELOPMENT OF MENTAL TRANSFORMATION ABILITIES 15 about gender differences can affect performance.…”
Section: Box 2 Sex Differencesmentioning
confidence: 99%
“…One such factor may lie in males experiencing more activities that involve spatial thinking compared to females (such as playing video games [79][80][81] …”
Section: Box 1 Distinctive Stimulus Featuresmentioning
confidence: 99%
“…A series of group difference and individual difference factors are of interest to us, such as whether people who are good "mental rotators", thus having high spatial competencies, might also rotate a digital map display more often, as previous work by Cohen and Hegarty (2007) suggests. A related question particularly relevant for 3D geo-browsers is whether participants who rotate paper maps when navigating in the real-world (Lobben 2004(Lobben , 2007, would also rotate an interactive map display more often when navigating in a digital world, or how familiarity with video games might influence the efficiency and effectiveness of decision making with interactive 3D displays, as shown by several authors outside of cartography (Feng et al 2007;Terlecki et al 2008). Furthermore, we ask whether experienced 3D geo-browser users might also tilt the display more often compared to 3D geo-browser novices, as Abend et al (2011) have shown.…”
Section: Empirical Studymentioning
confidence: 99%
“…In this context, Hegarty (2010) also mentions the influence of playing video games on spatial intelligence. While males seem to have significant advantages in mental rotation abilities (Linn and Petersen 1985;Voyer and Saunders 2004), gender differences in mental rotation can be reduced by playing video games for ten hours (Feng et al 2007;Terlecki et al 2008).…”
Section: Related Workmentioning
confidence: 99%